Differential regulation of detoxification enzymes in hepatic and mammary tissue by hops (Humulus lupulus) in vitro and in vivo. Issue 6 (20th March 2013) - Dietz, Birgit M.; Hagos, Ghenet K.; Eskra, Jillian N.; Wijewickrama, Gihani T.; Anderson, Jeffrey R.; Nikolic, Dejan; Guo, Jian; Wright, Brian; Chen, Shao‐Nong; Pauli, Guido F.; van, Richard B.; Bolton, Judy L.; et al.
<x xml:space="preserve">Abstract</x> Scope Hops contain the phytoestrogen, 8‐prenylnaringenin, and the cytoprotective compound, xanthohumol (XH). XH induces the detoxification enzyme, NAD(P)H‐quinone oxidoreductase (NQO1) in vitro; however, the tissue distribution of XH and 8‐prenylnaringenin and their tissue‐specific activity have not been analyzed. Methods and results An orally administered hop extract and subcutaneously injected XH were administered to Sprague–Dawley rats over 4 days. LC‐MS‐MS analysis of plasma, liver, and mammary gland revealed that XH accumulated in liver and mammary glands. Compared with the low level in the original extract, 8‐prenylnaringenin was enriched in the tissues. Hops and XH‐induced NQO1 in the liver, while only hops reduced NQO1 activity in the mammary gland. Mechanistic studies revealed that hops modulated NQO1 through three mechanisms. In liver cells, (i) XH modified Kelch‐like ECH‐associated protein leading to nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) translocation and antioxidant response element (ARE) activation; (ii) hop‐mediated ARE induction was partially mediated through phosphorylation of Nrf2 by PKC; (iii) in breast cells, 8‐prenylnaringenin reduced NQO1 likely through binding to estrogen receptorα, recruiting Nrf2, and downregulating ARE‐regulated genes. Conclusion XH and 8‐prenylnaringenin in dietary hops are bioavailable to the target tissues. While hops and XH might be cytoprotective in the liver, 8‐prenylnaringenin seems responsible for hop‐mediated NQO1 reduction in the mammary gland.